2008
DOI: 10.1128/iai.01528-07
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania pifanoiProteoglycolipid Complex P8 Induces Macrophage Cytokine Production through Toll-Like Receptor 4

Abstract: The P8 proteoglycolipid complex (P8 PGLC) is a glyconjugate expressed by Leishmania mexicana complex parasites. We previously have shown that vaccination with P8 PGLC provides protection against cutaneous leishmaniasis in susceptible BALB/c mice. However, the biological importance of this complex remains unknown. Here we show that P8 PGLC localizes to the surface of Leishmania pifanoi amastigotes and that upon exposure to macrophages, P8 PGLC binds and induces inflammatory cytokine and chemokine mRNAs such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 53 publications
2
37
0
3
Order By: Relevance
“…Furthermore, L. pifanoi P8 PGLC has been shown to induce TLR4-dependent macrophage cytokine and chemokine production (62). Our data provide evidence that TLR4 is also important during the early L. panamensis-macrophage interaction, since reduced TNF-␣ production and increased parasite survival occurred in TLR4 Ϫ/Ϫ infected mouse macrophages.…”
Section: Braziliensisinfected Myd88supporting
confidence: 59%
See 1 more Smart Citation
“…Furthermore, L. pifanoi P8 PGLC has been shown to induce TLR4-dependent macrophage cytokine and chemokine production (62). Our data provide evidence that TLR4 is also important during the early L. panamensis-macrophage interaction, since reduced TNF-␣ production and increased parasite survival occurred in TLR4 Ϫ/Ϫ infected mouse macrophages.…”
Section: Braziliensisinfected Myd88supporting
confidence: 59%
“…Bone marrow was harvested from mice as previously described (62), in accordance with the guidelines set forth by the University of Massachusetts Medical School and approved by its Institutional Animal Care and Use Committee. BMM precursors from WT (C57BL/6), MD-2…”
Section: Methodsmentioning
confidence: 99%
“…Structures analogous to LPS have been found in T. gondii, such as glycosylphosphatidylinositols (GPI) (9,36). Interestingly, all of these structures can trigger the activation of inflammatory cytokine expression by Toll-like receptor (TLR)-dependent pathways (25), e.g., TLR4 (10,47) and TLR2 (6,38). Some studies have revealed that LPS could induce the production of ROS in some organs, such as lung and liver (8,51), in which ROS are important to the pathogenesis of organ damage (52).…”
Section: Discussionmentioning
confidence: 99%
“…Also importantly, our findings indicate that macrophages may indeed be the major source of IFN-β in L. major infection in vivo , as previously suggested [53]. The difference between C57BL/6 and BALB/c in the TLR4-IFN-β-STAT-1-iNOS pathway in the absence of adaptive responses is a novel finding that substantiates previous conclusions that early mechanisms involving TLR4, IFN-β and NO [52][55], [58] are fundamental to host resistance.…”
Section: Discussionsupporting
confidence: 90%